Organic Farming in India: Present Status, Challenges and Technological Break Through - A. K. Barik (International Journal of Economic Plants)
Though the organic movement was initiated over a decade ago it has failed to gain the expected momentum due to several ambiguities. Organic farming is mostly envisaged as the stoppage of synthetic inputs and their replacement by organic alternatives i.e.use of organic manures and natural methods of plant protection instead of using synthetic fertilizers/pesticides. Organic agriculture relies on ecological processes, biodiversity and cycles adapted to local conditions, rather than the use of inputs with adverse effects. The major objectivity of organic farming resides on development of a self-sustainable farming system in harmony with nature which delivers ecologically and economically sustainable pure food with enrichment of surrounding biodiversity and its entire components. India holds a unique position among 172 countries practicing organic agriculture: it has 6, 50,000 organic producers, 699 processors, 669 exporters and 7,20,000 hectares under cultivation. India is poised for faster growth with the growing domestic market. Success of organic movement in India depends upon the growth of its own domestic markets. With the sizable acreage under naturally organic/default organic cultivation, India has tremendous potential to grow crops organically and emerge as a major supplier of organic products in the world’s organic market.